Succession planning for financial advisors : building an enduring business - Grau, David, Sr (John Wiley & Sons Inc., 2014)
This book is going to challenge you and everything you think you know about succession planning. For independent advisors, succession planning is quickly becoming the cornerstone to a strategic growth strategy designed to perpetuate their business and their income streams beyond their own lifetime, while providing a multi-generational service platform that attracts and rewards younger advisors. This makes succession planning one of the most, if not the most, important practice management tools in this industry today. As an independent financial advisor, now is the time to address the question of what will happen to your practice and your clients after you "exit the building." In most cases, the answers are right in front of you. Thankfully, Succession Planning for Financial Advisors: Building an Enduring Business has arrived to transform today's practices into businesses designed to endure and prosper and serve generations of clients. Learn how to create a "Lifestyle Succession Plan" that can provide a lifetime of income and benefits to the founder even as he/she gradually retires on the job Unlock the power of equity management - the best planning and building tool an independent advisor owns Learn how to attract and retain the best of the next generation to help you build a great business and to support your succession plans and care for your clients and their families Determine precisely when to start a formal succession plan and related continuity plan so that your business can work for you when you need it most Understand why succession planning and selling your business are completely different strategies, but how they can complement each other when used correctly 95% of independent financial service professionals are one owner practices. To the positive, these practices are among the most valuable professional service models in.